The role of Transforming Growth Factor (TGF) - Beta 1 Activated Kinase 1 (TAK1) in wound repair - Lam, Ivan Chee Ren (2013)
The generation of reactive oxygen species (ROS) is deregulated in several human pathologies, including cancer and diabetes. During the inflammatory phase of normal wound repair, the epidermal ROS levels are increased by the infiltrating phagocytic immune cells and the native keratinocytes. This inflammation-induced ROS production is tightly controlled to contain the oxidative damage, the mechanisms of which remain unclear. Transforming growth factor β–activated kinase 1 (TAK1) is a pivotal inflammatory mediator, and its expression is transiently elevated during wound healing, corresponding to the epidermal ROS production profile in the wound. However, the implications of this relationship remain obscure. Herein, we show that TAK1 directly regulates the expression of stem cell factor (SCF), which activates the protein kinase B (PKB)-α pro-survival pathway in a cell-autonomous manner to protect keratinocytes from ROS-mediated cell death. TAK1 deficiency in keratinocytes led to increased apoptosis in response to anoikis and TNF-α treatment and was associated with elevated ROS levels as determined by fluorescence activated cell sorting (FACS). Using organotypic skin co-culture and comparative growth factor array analysis, we revealed a cell-autonomous mechanism that involved the SCF/c-Kit/PKBα signaling cascade. The ectopic expression of TAK1 or treatment with exogenous recombinant SCF restored the increased ROS production and apoptotic cell death in the TAK1-deficient keratinocytes. Conversely, the normal keratinocytes treated with various inhibitors targeting the SCF/c-Kit/PKBα pathway exhibited increased ROS production and TNF-α– and anoikis-induced apoptosis. Our study reveals a novel antiapoptotic and protective role for SCF in keratinocytes and identifies TAK1 as a novel player uniting inflammation and ROS regulation in skin redox biology.